Phytosulfokine alpha enhances regeneration of transformed and untransformed protoplasts of Brassica oleracea - Vogrinčič, Valentin; Kastelec, Damijana; Murovec, Jana (Frontiers in Plant Science, 2024)
Phytosulfokine-α (PSK-α) is a disulfated pentapeptide (YIYTQ) acting as an intercellular signal peptide and growth factor. It was originally isolated from conditioned medium of asparagus mesophyll cell cultures in 1996 and later characterized as a hormone-like signal molecule with important roles in numerous processes of in vivo plant growth and development. It is currently becoming a valuable mitogenic factor in plant breeding and biotechnology due to its stimulatory effect on in vitro cell elongation, proliferation and differentiation. The focus of our work was to review current knowledge about the roles of PSK-α in plant biotechnology and to evaluate its influence on the regeneration of protoplasts of four Brassica oleracea cultivars (two cauliflower and two cabbage) cultured under two distinctive protocols and with different protoplast densities. Protoplast regeneration was studied due to its high value for plant genome editing, which is generally limited by the inefficient regeneration of treated protoplasts of numerous important plant genotypes. Our hypothesis was that the stress related to PEG-mediated protoplast transformation and the following decrease in viable protoplast density in culture could be alleviated by the addition of PSK-α to the culture medium. We therefore tested whether PSK-α could increase cell division at the early stages of culture (5 and 15 days after protoplast isolation) and stimulate the formation of microcallus colonies up to the 30st day of culture and to evaluate its influence on callus organogenesis leading to shoot regeneration. The PSK-α showed a strong stimulatory effect on untransformed protoplast regeneration already during the first days of culture, accelerating cell division up to 5.3-fold and the formation of multicellular microcallus colonies up to 37.0-fold. The beneficial influence was retained at later stages of regeneration, when PSK improved shoot organogenesis even if it was present only during the first 10 days of culture. The highest numbers of shoots, however, were regenerated when PSK was present during the first days of culture and later in solid shoot regeneration medium. Finally, the addition of PSK-α to PEG-transformed protoplasts significantly enhanced their division rate and the formation of microcallus colonies in selection media, up to 44.0-fold.